Meta-analysis of flecainide safety in patients with supraventricular arrhythmias - Wehling, Martin (Arzneimittelforschung, 2002)
Flecainide (CAS 54143-55-4) has been associated with increased mortality in patients with ventricular dysfunction and arrhythmias. It is a potent suppressant of supraventricular arrhythmias, but safety data for use in this condition are rare. A meta-analysis was performed including 122 prospective studies on the use of flecainide in patients with supraventricular arrhythmias and no significant signs of ventricular damage. 4811 patients on flecainide were included (mean age 55 ± 13 years, 60 % male). 38 studies were on i.v. Flecainide, 84 on p.o. application, 21 were placebo-controlled, 37 were comparative studies with other antiarrhythmics. The total exposure time was 2015 patient years, with a mean flecainide dose in p.o. studies of 216 ± 65 mg/day. The total database on flecainide contains the reports of 8 deaths (total mortality 0.166 %, mortality rate per 100 patient years 0.397). 3 deaths were non-cardiac deaths (cancer, suicide, urosepsis). Of the cardiac deaths, all but two occurred in patients with coronary heart disease. In controls, there was 1 death. Even for all deaths, this difference was not significant (p = 0.46). Proarrhythmic events were seen in 120 patients on flecainide, and, significantly more frequent, in 88 control patients (p < 0.001). The data clearly show that the use of flecainide in patients with supraventricular arrhythmias is safe and, because of its proven efficacy, advisable. Scrutiny should be exercised to diagnose all patients with structural left ventricular damage.